Análise bioeconômica do manejo do gato com esporotricose como estratégia de política pública - Gustavo Canesso Bicalho (2024)
Sporotrichosis, a neglected zoonosis with growing distribution in Brazil and South America, impacts the health and welfare of humans and animals, particularly domestic cats. Currently, despite Brazil having the highest incidence of sporotrichosis in the world and human treatment occurring through the Unified Health System (SUS), there is no nationally defined program to address this zoonosis. Given the severity of the disease, an economic analysis of public policies to address sporotrichosis is necessary. This study aimed to analyze the costs of treatment and neutering of cats, as much as the disposition of cat’s carcasses with sporotrichosis as a public policy through economic modeling and suggest priority parameters for its implementation, based on experiences published in the literature. The developed bioeconomic model allowed the simulation of feline sporotrichosis treatment in a population of 100,000 animals over a period of 365 days using @risk software. The proposed control program embraced diagnosis, appropriate treatment of positive animals, through multiple cycles, if necessary, with a protocol consistent with the characteristics of the animal and the clinical presentation, surgical sterilization of animals that recovered, euthanasia of animals that did not respond to treatment or faced severe conditions and had no owner, and incineration of carcasses of those who died, regardless of the cause. Parameters from the literature based on 15 articles and a Master's dissertation published between 2004 and 2024 were used, in addition to the database of the One Health Commission of the Minas Gerais Veterinary Medicine Council, referring to the care provided at UFMG and the City Hall of Belo Horizonte between the years 2020 to 2022 so that the mathematical model would reflect data close to reality. As a result, the estimated average annual cost per cat in a Sporotrichosis Control Program was R$ 1,848, including diagnosis (cytology and culture), treatment with Itraconazole and Potassium Iodide (if necessary), veterinary care every 30 days, additional tests (if necessary), neutering of the recovered (if not neutered), euthanasia (if necessary), and incineration of carcasses (if euthanized or deceased). Sensitivity analysis identified that the costs that most interfere with the total average value per animal are, in descending order, veterinary consultations, medications, neutering, and additional tests (hemograma, ultrasound, renal profile and hepatic profile). The majority of positive animals were males, intact, with access to the street, presenting three or more lesions in non-adjacent locations and without respiratory signs. The highest simulated cost was for a positive adult, intact animal, with respiratory signs and included in the two treatment cycles. Important factors for the implementation of a program to combat feline sporotrichosis are: easy access to diagnosis and medication, using active case-finding strategies through human cases; proper guidance for guardians; discharge at the right time, after 30 days of clinical cure or 60 days if the animal had respiratory signs, and euthanasia when the prognosis is unfavorable and the condition is incompatible with life, always decided ethically by a veterinarian; an ongoing ethical population management program; proper disposal of carcasses and health education occurring at all stages, mainly focused on topics such as responsible pet ownership and zoonosis prevention. With this cost, a treatment program during a one-year period would be able to cure approximately half of the positive animals, dispose of the carcasses of all those who evolved to death without putting other animals at risk from environmental contamination, and sterilize approximately half of the initially intact animals. The average cost per animal tends to decrease if the municipality purchases the medication through bidding and in larger quantities, as well as if it already has veterinary staff and an established ethical population management program. As cats are the main source of zoonotic sporotrichosis infection, it is concluded that positive feline management as a strategy for disease control in humans and animals could be implemented by Brazilian municipalities, along with population education actions, cat population management, and proper disposal of animals that die from the disease. Further studies are important to analyze the reduction of cases after the use of these strategies.